1983
DOI: 10.1128/iai.41.1.321-330.1983
|View full text |Cite
|
Sign up to set email alerts
|

In vitro inhibition of lymphocyte proliferation by Pseudomonas aeruginosa phenazine pigments

Abstract: Human lymphocyte proliferation is inhibited in vitro in the presence of killed Pseudomonas aeruginosa or cell-free P. aeruginosa culture supernatants. A comparison of culture supernatants obtained under similar conditions from Staphylococcus aureus, Escherichia coli, P. aeruginosa, and Pseudomonas cepacia strains demonstrated that all P. aeruginosa supernatants were strongly inhibitory, whereas supernatants from other bacteria were mildly inhibitory or not inhibitory at all. These P. aeruginosa inhibitors prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 31 publications
(27 reference statements)
3
25
1
Order By: Relevance
“…exotoxin A, a heat-labile protein, that was found to be cytotoxic in vitro for human peripheral blood macrophages and depressed lymphocyte proliferation and cytokine synthesis [22]. Furthermore, P. aeruginosa phenazine pigments and proteases have been described as inhibitors of lymphocyte activation and proliferation [23,24]. Other antigenic preparations have also demonstrated a stimulatory effect on gd T lymphocytes after heat treatment [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…exotoxin A, a heat-labile protein, that was found to be cytotoxic in vitro for human peripheral blood macrophages and depressed lymphocyte proliferation and cytokine synthesis [22]. Furthermore, P. aeruginosa phenazine pigments and proteases have been described as inhibitors of lymphocyte activation and proliferation [23,24]. Other antigenic preparations have also demonstrated a stimulatory effect on gd T lymphocytes after heat treatment [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…175*176 Lymphocyte functions may be blocked by bacterial products. 145 body, 1?7.156,157 correlated with disease progression.…”
Section: Lymphocytesmentioning
confidence: 99%
“…16' ) Most recently, Sorenson has demonstrated inhibition of lymphocyte proliferation in a nonspecific, reversible manner by P. aeruginosa pigments. 145 Other studies have revealed abnormalities in lymphocyte subpopulations. I7O During acute exacerbations, decreases in B lymphocytes and theophylline-resistant helper cells occur, while theophylline-sensitive suppressor cells are increased.…”
Section: Lymphocytesmentioning
confidence: 99%
“…A number of studies have shown that the opportunistic pathogen Pseudomonas aeruginosa can nonspecifically inhibit T-lymphocyte-mediated immunity in vitro (14,15,26,32,36) and in vivo (5,14,30). Patients infected with P. aeruginosa often show evidence of impaired cell-mediated immunity (28,33,34).…”
mentioning
confidence: 99%